Relationship Between Cadre Perception and Implementation of Integrated Primary Service Posyandu (ILP) as an Effort to Improve Primary Services - Ratih Kusuma Wardhani; Dwi Yuliawati; Gita Kostania (KHD Production, 2025)
Posyandu cadres play a strategic role as the spearhead of promotive and preventive services within the Integrated Primary Health Care (IPHC) framework. However, the extent to which cadres’ perceptions influence the actual implementation of ILP activities remains insufficiently understood. This study aims to analyze the association between cadres’ perceptions of the ILP Posyandu and its implementation. A descriptive analytical study with a cross-sectional design was conducted in October 2025 among 29 health cadres selected using purposive sampling. Data were obtained through structured questionnaires and analyzed using the Chi-square test. A total of 51.7% of cadres had negative perceptions of the ILP Posyandu, while 58.6% reported exemplary implementation. Statistical analysis showed no significant association between cadres' perceptions and ILP implementation (p = 0.176). Cadre’s perceptions do not significantly predict the implementation of ILP Posyandu. This suggests that ILP implementation is more strongly driven by systemic and structural factors such as supervision quality, training, and infrastructure availability rather than individual cadre understanding. Policy efforts should prioritize strengthening system-level support mechanisms to improve ILP Posyandu performance.